Layered in Time: Exploring the Impact of Nearly 8 Months of Stratification on Carbon Dynamics in a Mediterranean Reservoir. - Rodríguez-Gómez, Sofía; Montes-Pérez, Jorge; Ruiz Nieto, Miriam; Ledesma-Hernández, Guillermo; Warren-Jiménez, Paula; Conejo-Orosa, Teresa; Escot, Carmelo; Moreno-Ostos, Enrique (My University, 2024)
Ecosystem metabolism determines its role as a CO2 source or sink. In lakes and reservoirs, metabolism is conditioned by the phytoplankton community. This relationship was studied throughout a hydrological year in El Gergal, a Mediterranean mesotrophic and warm monomictic reservoir used for water supply to the city of Seville, Spain. Aerobic metabolic rates (respiration and primary production) were modeled using high-resolution data, including temperature, PAR, oxygen, salinity, and meteorological variables. The size structure of the phytoplankton community was examined using flow cytometry. Thermal stratification persisted for 7.7 months. During this period the aerobic ecosystem metabolism was autotrophic, with a net O2 production of 0.06 ± 0.03 mg l–1 day–1, and ultraphytoplankton (an intermediate size group between pico- and nanophytoplankton) dominated the community. Notably, the epilimnion was the only layer exhibiting net O2 production, while the metalimnion remained almost neutral and the hypolimnion was heterotrophic. During the mixing period, El Gergal was heterotrophic (net O2 consumption: 0.12 ± 0.03 mg l–1 day–1) with picophytoplankton (the smallest size group) dominating the community. On an annual scale, El Gergal reservoir was slightly heterotrophic, raising concerns about its role as a CO2 sink
Keywords: Ecosistemas mediterráneos; Salud de los ecosistemas; Carbono - Almacenamiento geológico; Carbon; Metabolism; Reservoir; Global change; Water sinking